Appendicitis in a Newborn: Case Report and Review of the Literature - Ivanova, Eleonora; Garunkštienė, Rasa; Liubšys, Arūnas (Acta medica Lituanica, 2022)
Background: Acute appendicitis in a newborn is rare and may be fatal. The reported incidence is 0,04 % to 0,2 %. Diagnosis remains challenging as the symptoms are undefined. Case presentation: Here we present a full-term newborn boy of 9 days presenting with malaise, reluctance to feed and subfebrile fever. Over the course of 6 days his condition became worse. The newborn was febrile, passed no stool and his stomach became distended. Perforation due to necrotizing enterocolitis was highly suspected. The diagnosis of acute appendicitis was finalized perioperatively after the perforation and worsening condition made the emergency surgery inevitable. After 16 days of admission the patient was discharged in good condition. Conclusion: Appendicitis in neonates is a dangerous yet manageable condition. While rare it should be included in differential diagnosis when presented with atypical necrotizing enterocolitis or unexplained peritonitis. Quick and accurate diagnosis may increase survival rates.